Inclusive Communication Model: Phenomenological Workplace Experiences of Deaf Workers in Pontianak - Saputra, Dimas; Rosnani, Titik; Jaya, Arman; Fahruna, Yulyanti; Marumpe, Dody Pratama (CV. Ulil Albab Corp, 2026)
The findings reveal an